2008
DOI: 10.1143/jjap.47.1333
|View full text |Cite
|
Sign up to set email alerts
|

Direct Electrochemistry of Hemoglobin Molecules Adsorbed on Bare Indium Tin Oxide Electrode Surfaces

Abstract: Previously, we proposed to set ultrasound (US) beam-forming parameters in order to realize the required point spread function (PSF) on the basis of optimization theory. In this report, for high quality-lateral cosine modulation (LCM) US imaging and measurements of accurate displacement vector and elasticity (i.e., strain tensor, shear modulus), after briefly reviewing our trials that broke away from the use of the Fraunhofer approximation to determine the apodization function, images and measurements obtained … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 43 publications
0
9
0
Order By: Relevance
“…by the MET types (Kafi and Crossley, 2013;Yin et al, 2005;Revenga-Parra et al, 2005;Topoglidis et al, 2003;Kawahara and Ohno, 1998;Shan et al, 2007;Shi et al, 2007;Zhao et al, 2006;Feng et al, 2006;Zhang and Oyama, 2004;Jia et al, 2004;Sun and Hu, 2004;Gu et al, 2001). On the other hand, we have demonstrated a simplest DET between Hb molecules and bare indium-tin-oxide (ITO) electrodes and found that the protein structure of Hb molecules on the bare ITO electrode surface should be similar to its own native state the same as that in the solution phase (Ayato et al, 2008;Ayato et al, 2007). Recently, we have developed a novel BFC cathode based on the simplest DET of the Hb molecules, reducing hydrogen peroxide (H2O2) to water, on the bare ITO electrodes (Ayato and Matsuda, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…by the MET types (Kafi and Crossley, 2013;Yin et al, 2005;Revenga-Parra et al, 2005;Topoglidis et al, 2003;Kawahara and Ohno, 1998;Shan et al, 2007;Shi et al, 2007;Zhao et al, 2006;Feng et al, 2006;Zhang and Oyama, 2004;Jia et al, 2004;Sun and Hu, 2004;Gu et al, 2001). On the other hand, we have demonstrated a simplest DET between Hb molecules and bare indium-tin-oxide (ITO) electrodes and found that the protein structure of Hb molecules on the bare ITO electrode surface should be similar to its own native state the same as that in the solution phase (Ayato et al, 2008;Ayato et al, 2007). Recently, we have developed a novel BFC cathode based on the simplest DET of the Hb molecules, reducing hydrogen peroxide (H2O2) to water, on the bare ITO electrodes (Ayato and Matsuda, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…In the last decade, a few studies have been conducted on mammalian's Hb, for example, Topoglidis et al [6] reported that titanium oxide and tin oxide allow the reduction of bovine metHb without the addition of any promoters and mediators. Later, Ayato et al [7,8] reported that tin-doped indium oxide can induce the electron transfer of the haem (Fe III /Fe II ) redox center in bovine Hb molecules; they also found that the protein directly adsorbed on the electrode surface was not significantly denatured. More recently, Martinez-Mancera and Hernandez-Lopez [9] reported that thin films of solid solutions like In 2-x Sn x O 3 on flat glass substrates can act as both electron acceptors and electron donors, and can be considered a simple model system for mimicking a charge interface of the physiological-binding domain.…”
Section: Introductionmentioning
confidence: 99%
“…Especially cytochrome c (cyt.c) is one of the most extensively studied proteins because of its ET reaction activity. [1][2][3][4][5]8,9 However, still now controlling the protein ET reaction is difficult because of many technical issues. One of them for cyt.c electrochemistry adsorbed on ITO electrode is a lack of adsorption ability of cyt.c for long-time duration.…”
Section: Introductionmentioning
confidence: 99%